The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/12538078.2004.10515440
|View full text |Cite
|
Sign up to set email alerts
|

Les peroxydases végétales de classe III

Abstract: Mots c/es : peroxydases -reactions catalytiques -role physiologique.Abstract.-Peroxidases are heme proteins involved in the oxidization of a large variety of substrates, through the reaction with hydrogen peroxide. Plant peroxidases are class Ill peroxidases, according to nomenclature. Primary and tertiary structure, as well as principles of reactions catalyzed by such peroxidases are discussed. Class Ill peroxidases are involved in different physiological functions, such as cell wall metabolism, hormonal meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 205 publications
0
18
0
Order By: Relevance
“…It is known that enhanced H 2 O 2 formation, especially when exacerbated by increased NADH oxidase activity, decreases cell wall extensibility [8]. Moreover, it has been suggested that the polymerization of monolignols to lignin is mediated by the interaction of two types of peroxidases: NADH oxidase and coniferyl alcohol peroxidase (EC 1.11.1.4) [9]. NADH oxidase catalyzes the generation of H 2 O 2 during the oxidation of monolignols and coniferyl alcohol peroxidase polymerizes monolignol (coniferyl, synapyl, p-coumaryl alcohol) to lignin [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that enhanced H 2 O 2 formation, especially when exacerbated by increased NADH oxidase activity, decreases cell wall extensibility [8]. Moreover, it has been suggested that the polymerization of monolignols to lignin is mediated by the interaction of two types of peroxidases: NADH oxidase and coniferyl alcohol peroxidase (EC 1.11.1.4) [9]. NADH oxidase catalyzes the generation of H 2 O 2 during the oxidation of monolignols and coniferyl alcohol peroxidase polymerizes monolignol (coniferyl, synapyl, p-coumaryl alcohol) to lignin [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the polymerization of monolignols to lignin is mediated by the interaction of two types of peroxidases: nicotinamide adenine dinucleotide (NADH) oxidase and coniferyl alcohol peroxidase (EC 1.11.1.4). NADH oxidase catalyzes the generation of H 2 O 2 during the oxidation of monolignols, and coniferyl alcohol peroxidase polymerizes monolignol (coniferyl, synapyl, and p-coumaryl alcohol) to lignin [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the case of aluminium, several researches have reported that Al treatment was marked by a significant stimulation on peroxidases activities [1,2]. These enzymes have been involved in several processes such as cell wall rigidification [3], auxin catabolism [4], ethylene metabolism [5] and stress responses [6]. In fact, it has been reported that peroxidase induction is a general response of higher plant to metallic stress conditions [7].…”
Section: Introductionmentioning
confidence: 99%